The impact of socio-economic status and sanitation levels on the prevalence of diarrhoeal diseases in the Akim Oda area of Ghana - Fening, K.O.; Edoh, D.A. (Internet Scientific Publications, 2009)
A survey was conducted between August and October, 1998 in Akim Oda area of Ghana to relate socio-economic differences, as measured by income, education, occupation and housing, among residents in three communities to diarrhoea prevalence. There was clinical and laboratory diagnosis of cholera and administration of structured interview-administered questionnaires to find from residents their demographic, socio-economic, health practices and status, and to seek their opinions on cholera transmission, control and prevention. The survey revealed that residents from Old-town and Aduasa belong to low social class and was reflected in their high illiteracy, unemployment rates and associated poor sanitation. As such, they had the highest prevalence of diarrhoeal diseases. Contrarily, residents from Quarters residential area were found to belong to high social class, which was reflected in their high literacy, employment rates and good sanitation. As such, they had no case of diarrhoea. The underlying factors responsible for this epidemic are discussed.
Keywords: Socio-economic status; diarrhoeal disease transmission; cholera; sanitary conditions; insanitary conditions